Distress Trajectories for Parents of Children With DSD: A Growth Mixture Model. (16th February 2021) - Perez, Megan N; Clawson, Ashley H; Baudino, Marissa N; Austin, Paul F; Baskin, Laurence S; Chan, Yee-Ming; Cheng, Earl Y; Coplen, Douglas; Diamond, David A; Fried, Allyson J; Kolon, Thomas; Kropp, Bradley; et al.
Abstract: Objective: This study identifies trajectories of parent depressive symptoms after having a child born with genital atypia due to a disorder/difference of sex development (DSD) or congenital adrenal hyperplasia (CAH) and across the first year postgenitoplasty (for parents who opted for surgery) or postbaseline (for parents who elected against surgery for their child). Hypotheses for four trajectory classes were guided by parent distress patterns previously identified among other medical conditions. Methods: Participants included 70 mothers and 50 fathers of 71 children diagnosed with a DSD or CAH with reported moderate to high genital atypia. Parents were recruited from 11 US DSD specialty clinics within 2 years of the child's birth and prior to genitoplasty. A growth mixture model (GMM) was conducted to identify classes of parent depressive symptoms over time. Results: The best fitting model was a five-class linear GMM with freely estimated intercept variance. The classes identified were termed "Resilient, " "Recovery, " "Chronic, " "Escalating, " and "Elevated Partial Recovery." Four classes have previously been identified for other pediatric illnesses; however, a fifth class was also identified. The majority of parents were classified in the "Resilient" class (67.6%). Conclusions: This study provides new knowledge about the trajectories of depressive symptoms for parents of children with DSD. Future studies are needed to identify developmental, medical, or familial predictors of these trajectories.